MORPHOLOGICAL AND ANATOMICAL STUDY OF JUNIPERUS HEMISPHAERICA C. PRESL. FROM CUPRESSACEAE FAMILY - F. K. Serebryanaya; I. V. Karpenko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
We have conducted morphological and anatomical studies of Juniperus hemisphaerica, revealed diagnostic indices of lamina, stem, needles.